Teenage witches : magical youth and the search for the self - Berger, Helen A., 1949-; Ezzy, Douglas (UPCC book collections on Project MUSE., 2007)
A popular new image of Witches has arisen in recent years, due largely to movies like The Craft, Practical Magic, and Simply Irresistible and television shows such as Buffy the Vampire Slayer, Sabrina the Teenage Witch, and Charmed. Here, young sexy Witches use magic and Witchcraft to gain control over their lives and fight evil. Then there is the depiction in the Harry Potter books: Witchcraft is a gift that unenlightened Muggles (everyday people) lack. In both types of portrayals, being a Witch is akin to being a superhero. At the other end of the spectrum, wary adults assume that Witches engage in evil practices that are misguided at best and dangerous at worst. Yet, as Helen A. Berger and Douglas Ezzy show in this in-depth look into the lives of teenage Witches, the reality of their practices, beliefs, values, and motivations is very different from the sensational depictions we see in popular culture.